Sports injuries in elite football players: classification, prevention, and treatment strategies update - Zeng, Yinping; Ji, Weiguo; Shi, Yu; Liu, Wenduo; Ji, Weiping (Frontiers in Sports and Active Living, 2025)
Elite football players are particularly vulnerable to sports injuries due to the demands of high-intensity training and competition, which negatively affect their athletic careers and the economic interests of their clubs. Currently, the structural classification of injury scenarios and types in football remains unclear, hindering players' understanding of injuries and the implementation of effective preventive measures. This study aims to refine the structural classification of football-related injuries and update the corresponding scenarios, prevention strategies, and treatment approaches for general sports injuries, degenerative injuries, and accidental injuries. Researchers screened relevant literature from PubMed, SportDiscus, and Google Scholar databases from May 2000 to May 2025. For general sports injuries, skeletal muscle injuries (muscle fiber injuries, tendon injuries) can be prevented through eccentric strength training, while joint injuries (ligament injuries, muscle imbalances) require a focus on neuromuscular control training. Degenerative injuries necessitate systematic treatment, and surgical intervention should be adopted, when necessary, followed by a personalized rehabilitation program. Accidental injuries (concussions and fractures) can be mitigated using protective gear, rule modifications, and enhanced safety measures education. This article emphasizes the importance of a structured classification system for injury prevention and differentiated treatment strategies for elite football players. This will provide a theoretical basis for establishing clear understanding among individual athletes and reducing the occupational risk of injury in football.